Positive Aspects of the Caregiving Experience: Finding Hope in the Midst of the Storm. Issue 3 (2nd July 2016) - Walker, Ruth V.; Powers, Sara M.; Bisconti, Toni L.
Abstract : Throughout the caregiving literature, few researchers have utilized positive aspects of care (e.g., satisfaction) to help understand the caregiving experience. This study utilized a survey approach to better understand how positive aspects of care relate to the caregiving experience of 70 informal female caregivers of older adult care receivers living with a chronic illness or disability. Positive aspects of caregiving were significantly related to burden, depression, identity loss, and role captivity. Regression analyses indicate positive aspects of care moderate the relationship between burden and depression. Results support the importance of: working with women providing informal and unpaid care to make visible the micro, meso, and macro level forces shaping their caregiving experience; helping clients identify and enact strategies for reducing burden as well as find meaning in their caregiving role; helping clients to identify strengths and sources of personal and relational empowerment; and the need for culturally competent practice.